Ethnobotanical knowledge of medicinal plants in the Don Pu Ta Forest by Kaloeng Ethnic Group, Sakon Nakhon Province, Northeastern Thailand - SOMBAT APPAMARAKA; SURAPON SAENSOUK; PIYAPORN SAENSOUK; AUEMPORN JUNSONGDUANG; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2023)
Abstract. Appamaraka S, Saensouk S, Saensouk P, Junsongduang A, Setyawan AD. 2023. Ethnobotanical knowledge of medicinal plants in the Don Pu Ta Forest by Kaloeng Ethnic Group, Sakon Nakhon Province, Northeastern Thailand. Biodiversitas 24: 4617-4635. Don Pu Ta Forest (in Thailand) is a vital conservation area with significant natural resources that are intertwined with the way of life, traditions, beliefs, and culture of the local community. This ecosystem fosters interdependence among its components. The local healers rely on the medicinal plants found in the Don Pu Ta Forest to provide healthcare to the people in their community. This research aimed to investigate the plant diversity, ethnobotanical knowledge, and medicinal plant utilization in the Don Pu Ta Forest, specifically within the Kaloeng Ethnic Group of Sakon Nakhon Province, Thailand. Data were collected through semi-structured interviews involving three indigenous healers and 220 local residents between January 2016 and November 2017. The interviews focused on plant usage, local names, utilized plant parts, methods of use, and medicinal properties. We also conducted vegetation analysis to assess the diversity and composition of vegetation in the Don Pu Ta Forest. The findings revealed that the Don Pu Ta Forest of the Kaloeng Ethnic Group in Sakon Nakhon Province contained medicinal plants from 28 families and 44 species. The biodiversity index (H') was calculated as 3.34, the Evenness Index (E) as 0.88, and the highest importance value index (IVI) as 25.26. Interviews with folk medicine healers identified the use of medicinal plants for treating 29 different symptoms. Notably, Micromelum minutum (Forst.f.) Wright & Arn., Rhodamnia dumetorum (DC.) Merr. & L.M. Perry, Garcinia cowa Roxb., and Casearia grewiifolia var. grewiifolia exhibited the highest Fidelity Level (FL) at 100%. The results of this study imply that ancestral wisdom's role in shaping the Kaloeng group's medicinal traditions, advocating for their integration with contemporary healthcare. In summary, the study offers valuable insights into the diversity, importance, and ethnobotanical use of medicinal plants in Don Pu Ta Forest, emphasizing possibilities for conservation, sustainable practices, and further exploration of these resources for healthcare benefits.